Literature Review: Implementasi Advokasi Kesehatan dalam Pencegahan dan Penanggulangan Tuberkulosis - , Arini Dwi Rahmadani; Raudhiyah Hasanah Rambe; Dinda Purnama Sari; Fatimah Az Zahra Lubis; Miftahurrahmah El Hayatli (Lembaga Pengembangan Kinerja Dosen, 2026)
Tuberculosis remains a public health problem in Indonesia, with a relatively high number of cases and mortality rates. The success of tuberculosis control programs requires various efforts, one of which is health advocacy aimed at gaining policy support, funding, and the involvement of various parties in disease prevention and control. This study aims to analyze the implementation of advocacy in tuberculosis prevention and control and identify the roles and obstacles that influence the success of TB control programs. The method used was a literature review with a qualitative descriptive approach. Articles were obtained through Google Scholar using keywords related to health advocacy and tuberculosis. A total of 10 articles that met the inclusion criteria were analyzed descriptively to identify the implementation, benefits, and obstacles of advocacy in tuberculosis control. The results of the study indicate that the implementation of health advocacy plays a role in increasing public knowledge, strengthening cross-sector partnerships, supporting early case detection, improving treatment adherence, reducing stigma against sufferers, and encouraging policy support and empowering health cadres. However, its implementation still faces obstacles such as limited funding, suboptimal policy support, low community participation, and weak cross-sector coordination. Therefore, it is necessary to strengthen advocacy through increased government commitment, adequate budget support, and community empowerment so that the tuberculosis control program can run more effectively and sustainably.